Eucalyptus in Riclamation of Saline and Alkaline Soils in India - Mathor, N. K.; Sharma, A. K. (Indian Forester, 1984)
The Saline and Alkaline soils cover nearly 7 million ha of land occurring in as many as 14 states of India. It is indeed a challenging task to afforest these aresS since most of the indigenous and exotic species are not tolerant of soil alkalinity and salinity. Eucalyptus plantation programme has gained momentum during the recenl past under social forestry and farm forestry programmes. Eucalyptus are easy to propagate and require little care. Their rate of growth and biomass production is high and has attracted the attention of foresters as well as the general public. Barren lands have been considered best for planting fast growing adaptable exotic and indigenous spedes. Many Eucalyptus species and their salt resistant provenance may be of utmost importance for afforesting the salt affected and alkalinity affected soils in various regions in India. More genetical reseach is essential to locate suitable provenances to plant them in these salt and alkall affected areas. Eucalyptus species growing in the homoclimatic zones in Australia under saline and alkaline soils may prove of great help in successCully afforesting such tracts in various regions of India. The climatic, ecotypic and soil conditions of the environment where there species or their strains occur in Australia needs thorough study. Studies are also required to discover and locate identical locations in India for trying these species and strain of Eucalyplus. Eucalyptus comoldurensis is a potential species for this purpose and its new provenances and strains need exploratory research. It is advisable that under seed exchange programme more stress should be laid on procuring seeds of such available provenances of E. camaldulensis which occur in saine and alkaline solis in Australia. Inter specific hybridization for evolving salt and alkali resistant strains of Eucalyptus is expected to case the problem of afforestation in saline and alkaline solis.